Collected Works of Erasmus : Spiritualia, Volume 66 - Erasmus, Desiderius, -1536 (Book collections on Project MUSE., 1988)
This is the first of five volumes to appear in the section of the CWE devoted to Erasmus' spiritualia, works of spirituality that include such aspects of religion as piety, theology, and the practice of ministry.